Faktor-Faktor Yang Berhubungan dengan PHBS di Pekanbaru - Vivi Julianingsih; Tri Krianto Karjoso; Elly Satriani Harahap (STIKes Payung Negeri Pekanbaru, 2020)
Clean and healthy life behavior in the household is an effort to empower household members to be able to practice clean and healthy behavior. Indonesia has a target of achieving Clean and Healthy Life Behavior in households that is 100% and for Simpang Baru Puskesmas the achievement is 62.1%, still lower than the National achievement target. This type of research is quantitative cross sectional research design. Samples were taken by cluster sampling technique with a total sample of 380 households. Data analysis starts from univariate analysis, bivariate analysis, and multivariate analysis. The results obtained by the Head of the Family (KK) who do not have PHBS in the household arrangement of 216 people (56.8%) and independent variables that have a significant relationship are variables: culture (POR = 3.092), the role of health workers (POR = 2.018 ), education (POR = 1.979), and knowledge (POR = 1.665). Meanwhile, the attitude variable is confounding to the cultural variable. It is recommended that health workers, especially those in charge of health promotion at the Simpang Baru Health Center, increase community knowledge by providing information and education on an ongoing basis in implementing PHBS life in the household setting.